The ice house [videorecording (DVD)] - Fywell, Tim; Craig, Daniel, 1968-; Redgrave, Corin; Aldridge, Kitty, 1962-; Barber, Frances, 1958- (BBC Video ; Distributed by Warner Home Video, 2012)
Ten years ago, Phoebe Maybury's hateful husband David disappeared from Streech Grange. Now, a naked, unidentifiable corpse has been discovered in the icehouse on the Grange and Inspectors Walsh and McLoughlin have to decide whose it is, whether he was murdered; and who killed him.